Design driven strategies Visioni a confronto - TRIVELLIN, ELEONORA; Trivellin, Eleonora (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
The collection of contributions in this volume looks forward, and also backward, regarding the centrality of design between new and traditional production systems, space-environment-sustainability, and identity. The role of the project in defining forms, material and immaterial, is crucial for their understanding and, consequently, for building participation. In the majority of the interventions, there is an underlying desire to increase the social dimension of design through participatory practices. In other words, we could say that there is a desire to give a political dimension to the project in the fullest sense of the word. Regaining this dimension can be strategic and to do this it is perhaps necessary to understand how the relationship between design-production work has changed and how it will change.